The Use of Passive Voice in Political Newspaper Articles: A Descriptive Analysis of Its Frequency and Functions - Nita Sitta Rachma; Anwar Fadila; Desy Awal Mar’an; Tarina Dashela (EDU SOCIETY: JURNAL PENDIDIKAN, ILMU SOSIAL DAN PENGABDIAN KEPADA MASYARAKAT, 2025)
In written English production, using passive voice is one of the most challenging aspects to master. This study aims to analyze the frequency, structure, and functions of passive voice in written English, especially in political newspaper articles. A descriptive qualitative approach was used for this study, with data collection techniques in the form of document studies on four samples of newspaper articles regarding political issues that happened in Indonesia in early 2025; two articles were taken from The Jakarta Post, and two others were from ANTARA, published around January to February 2025. The result obtained from 4 political news articles shows that of the total 82 sentences analyzed, 26 sentences (31%) are passive voices. Two main types found were: "to-be" passive form (formal passive), 75%, and "to get" passive 25%. This indicates that passive sentence usage in political news articles is quite common. The passive form, with or without phrases, is used by the writers to emphasize some truths to be involved in an event or incident and express their opinion to influence the reader's mind.